Enhancement of backscattering by a conducting cylinder coated with gradient metasurface - Shang, Yuping (2017)
This paper proposes a highly effective method for enhancing the backscattering by a conducting cylinder that is coated with a gradient metasurface. The employed metasurface exhibits a phase gradient continuously varying along the circumferential direction of the cylinder so that in-phase retroreflection can be produced to enhance the backscattering. It is demonstrated that the cylinder coated with the proposed gradient metasurface can generate backscattering very close to that from a conducting plate with the same dimensions as the cylinder's cross-section perpendicular to the incident plane wave. Compared with a bare conducting cylinder, the backscattering is significantly enhanced by the gradient metasurface made of conducting strips printed on a grounded dielectric substrate. Effects of cell numbers along the cylinder axis, incident angle, and polarization of the incoming electromagnetic wave on the backscattering enhancement are examined and discussed. A good agreement between simulated and measured backscattering results validates the observations.